Anaerobic Co-digestion with different concentrations of whey and cow dung in biogas production. - Cieza-Rimarachin, Y. (2023)
In this research, the whey potential for optimization of biogas production by anaerobic co – digestion with cow dung was studied. It used a two-component multifactorial – design, where it was studied four batch type - biodigesters of 4 liters on a laboratory scale with different whey concentrations (0%, 10%, 30%, 50%) and dilute cow dung in relation 1:1.5, each one in three replications. The experimentation was performed under temperature control of 35°C±2°C; and pH control between 6.4 to 6.9 by the addition of NaOH 3N; with an average of 7% of total solids and a holding time of 35 days. Below these conditions, the 2nd biodigester with 10% of whey, it was the one which generate the largest amount of biogas with 37.9 liters in total; the 3rd biodigester, with 30% of whey generates 24.2 liters of biogas; and the 4th biodigester, with 50% of whey generates 14.5 liters. The reduction of total solids in biodigesters were 38.5%, 43.4%, 40.2% and 27.6% respectively. We used the Gompertz model, which allowed us to find high correlation grades oscillating between 86.295% y 94.268%. Therefore, it can be established, that the use of whey duplicates the biogas production until 52% and sets a limit of 30% (v/v) to obtain a good biogas production in batch-type biodigesters.